Evaluation of family medicine identity levels and personality types among family medicine residents and specialists - Mustafa Metehan Demirel; İsmail Kasım; Erhan Şimşek (Turkish Journal of Family Practice, 2026)
Objective: This study aimed to examine the association between family physicians’ professional identity and Enneagram-based dominant personality types, and to explore whether professional identity scores vary across personality patterns. Methods: This descriptive cross-sectional study was conducted between June 5-September 1, 2025, among family medicine residents and specialists who had completed residency training at the same tertiary training institution in Türkiye. Of 230 invited physicians, 218 participated (response rate: 94.8%); after excluding three outliers, analyses were performed on 215 physicians (122 residents, 93 specialists). Data were collected using a sociodemographic form, the Family Medicine Identity Scale (FMIS; 46 items; subdimensions: physician–patient communication, professional satisfaction, scope of work/comprehensive approach, biopsychosocial approach) and the Taştan Personality Type Inventory (44 items; nine Enneagram types). Due to the cross-sectional design, causal inferences cannot be drawn. Results: No significant differences were found in total or subscale FMIS scores across any dominant Enneagram personality type (all p>0.05). Effect sizes for all non-significant comparisons were small (η² range=0.008–0.045). The mean total FMIS score was 71.28±9.35. The most frequent dominant personality types were Type 1 (27.9%) and Type 2 (25.1%). Conclusion: These findings suggest that professional identity strength in family medicine may be shaped more by shared specialty norms and training than by dominant personality type. We recommend future longitudinal and qualitative studies to further explore how different personality types enact family medicine identity in practice.